Watching the emergence of a Fano resonance in doubly excited helium - Blättermann, Alexander; Kaldun, Andreas; Stoob, V.; Donsa, Stefan; Wei, Hui; Pazourek, Renate; Nagele, Stefan; Ott, Christian; Lin, Chii-Dong; Burgdörfer, Joachim; Pfeifer, Thomas (My University, 2017)
We report on the experimental observation of the buildup of the 2s2p Fano resonance in helium in the time domain, which has been under theoretical investigation for more than a decade. The emergence of the absorption line is temporally resolved by interrupting the natural decay of the excited state via saturated strong-field ionization at a variable time delay. We compare the experimental data with full ab-initio simulations to validate the time-gating by strong-field ionization and thereby confirm the recently developed theory for the formation of Fano line-profiles.
Keywords: Fano resonance; Doubly Excited helium; absorption line; natural decay